Fenomena Speeding serta Ancamannya dalam Keselamatan Lalu Lintas di Wilayah Hukum Kepolisian Resor Buleleng - Ketut Suryawan; Ni Putu Rai Yuliartini; Dewa Gede Sudika (Mahkamah : Jurnal Riset Ilmu Hukum, 2026)
This research aims to examine and analyze the phenomenon of speeding and illegal racing, which poses a significant threat to traffic safety within the legal jurisdiction of the Buleleng Resort Police (Polres Buleleng). The study employs empirical legal research methods, gathering primary data through observations and interviews with traffic police officers, alongside secondary data from legal literature and previous studies. The findings indicate that the speeding phenomenon in Buleleng is predominantly carried out by teenagers and young adults, often motivated by social media trends, peer pressure, and the search for identity. This reckless behavior leads to a high rate of traffic accidents, frequently resulting in severe injuries or fatalities. Furthermore, law enforcement efforts by Polres Buleleng face several challenges, including the high mobility of the perpetrators, lack of personnel during specific hours, and low legal awareness among the public. Preventive measures such as counseling in schools and repressive measures like electronic traffic law enforcement (E-TLE) and routine patrols need to be optimized. This study concludes that an integrated approach involving the police, educational institutions, and parents is crucial to mitigating the speeding phenomenon and ensuring traffic safety.